A descriptive study of the awareness of niche marketing for commercial design practice among interior designers in relation to business plan management - Roque, Krystal Shayne D.; Florendo, Raquel Baltazar (2011.)
This research focused on the awareness of commercial designers of niche marketing which is a specialty that focuses its services on a target group of clients. The study aimed to answer the following research questions: (1) How is awareness of niche marketing related to local practice? (2) In what way niche marketing is related to business plan management? (3) What are the factors affecting or indicating the level of awareness? The study determined the level of awareness of niche marketing among interior designers with the general objective of determining the level of awareness of interior designers of the concept of niche marketing. Using purposive and snowball sampling, twelve (12) licensed interior designers with at least two years of commercial design practice were selected for the study. Data was gathered through the use of survey questionnaire. Answers were summarized and tabulated into figures. Results of the survey showed some interior designers were unfamiliar about niche marketing as to its scope and definition. On the contrary, designers knew that business and marketing plan is necessary in niche marketing however the use of it was of a little importance to some designers. The factors which affected the designers' level of awareness were practice and promotion, colleagues, and internet. Findings suggest that specialization exists but the actual practice of niche marketing was unclear. Hence, interior designers were not fully aware of niche marketing. This study recommends that business plan management is necessary in niche marketing. More related literature about the local niche marketing practices should be published. Collaboration with other disciplines like Business Administration will also help future researchers to deepen more the approach and understanding of the topic.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Market segmentation -- Philippines